Transformation of the Risks to Economic Security and Their Destructive Impact on the Economic Sustainability of the Country and the Achievement of an Appropriate Level of the Economic Security of Ukraine - Lutsyk Yulia O. (Problemi Ekonomiki)
Today’s security environment is characterized by a high level of turbulence and unpredictability. The living conditions of Ukraine require an in-depth analysis of issues related to the need for gradual and planned recovery and strengthening of the country’s economic stability, as well as ensuring an adequate level of economic security of the State in the face of losses and restrictions from the war. The aim of the scientific article is to analyze the prospects and problematic issues of economic security of the State related to the transformation of risks and threats to economic security in the conditions of a long-term war, to study their negative consequences that need to be studied and solved, especially in the context of prolongation and aggravation of the war. The article analyzes the challenges and threats that emerged in 2022 as a result of russia’s full-scale armed aggression against Ukraine and continue to have a negative impact on the country’s economy and the overall level of economic security in 2023–2024. The impact of risks and threats has been analyzed, the most vulnerable components of the country’s economic security have been identified: foreign economic, financial, social, investment and innovation. Measures to minimize risks in order to achieve the economic stability of the country and restore the proper level of economic security of Ukraine are proposed. The importance of identifying trends and factors that will contribute to the recovery of the national economy of the State is substantiated. In the course of the analysis, it is concluded that the current reaction of the economy to the losses and restrictions of the war has revealed unexpected resilience to the shock effects of risks and threats. Thus, if the factors of stabilization of the country’s economic security are preserved, we can expect positive prospects for ensuring the country’s economic stability and achieving an appropriate level of economic security of the State.